KONSERVASI ALAM: AKTIFITAS PAGUYUBAN MASYARAKAT PEDULI HUTAN (PMPH) DALAM BINGKAI LIVING QUR’AN DI KABUPATEN KUDUS - Salma Fa'atin; Nailis Sa’adah (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2018)
Nature Conservation: Activities of the Paguyuban Masyarakat Peduli Hutan (PMPH) Society in the Living Qur'an Frame in Kudus Regency. This paper discusses the nature conservation activities carried out by the community of “Paguyuban Masyarakat Peduli Hutan (PMPH)” in Colo village, Dawe district, Kudus district. The focus of the study is to uncover PMPH activities in the living study of the Qur'an using the phenomenology paradigm. The study was conducted with a qualitative approach. Data collection is done by interview techniques, documentation, and observation. The results of the study found that the community of “Paguyuban Masyarakat Peduli Hutan (PMPH)” in Colo village, Dawe district, Kudus Regency had carried out activities / behaviors (living Qur'an) which actually constituted the values ​​of the Koran concerning the duty of mankind to maintain and preserve the universe in order to bring benefits and prosperity to the people. The concept of ihsan, taskhir and ta'mir has manifested itself in the action of PMPH. Manifestation of social and individual piety, worship and charity charity created in PMPH slogan